Sams teach yourself Windows 8.1 apps with XAML and C♯ in 24 hours - Nathan, Adam, 1977- (Sams teach yourself., 2014)
Learn how to build great Windows Store apps! Figures and code appear as they do in Visual Studio. In just 24 sessions of one hour or less, Sams Teach Yourself Windows 8.1 Apps with XAML and C# in 24 Hours will help you build compelling apps for Windows 8.1 devices of all kinds. Using this book's straightforward approach, you'll learn to design and build apps, create flexible user interfaces, handle inputs, integrate controls, and more. Step by step, you'll discover how to leverage XAML's visual richness and the immense power of Windows 8.1. Every lesson builds on what you've already learned, giving you a rock-solid foundation for real-world success! Step-by-step instructions carefully walk you through today's most common XAML and C# development tasks. Quizzes at the end of each chapter help you test your knowledge. Notes present interesting information related to the discussion. Tips offer advice or show you easier ways to perform tasks. Cautions alert you to possible problems and give you advice on how to avoid them. Learn how to ... Create user interfaces that adapt to any device, from tablets to high-def TVs Handle input from touch, mouse, pen, and keyboard Manage the entire Windows 8.1 app lifecycle and all execution states Master powerful XAML controls for text, images, audio, video, and more Integrate vector graphics that scale perfectly to any size Apply rich animations Work with styles, templates, and visual states Exploit the Windows charms within your apps Take full advantage of data binding and contracts Read data from sensors and control external devices Provide dynamic updates via live tiles, notifications, and the lock screen Discover the many ways to monetize your Windows Store apps.